EACVI recommendations on cardiovascular imaging for the detection of embolic sources: endorsed by the Canadian Society of Echocardiography. (12th March 2021) - Cohen, Ariel; Donal, Erwan; Delgado, Victoria; Pepi, Mauro; Tsang, Teresa; Gerber, Bernhard; Soulat-Dufour, Laurie; Habib, Gilbert; Lancellotti, Patrizio; Evangelista, Arturo; Cujec, Bibiana; Fine, Nowell; et al.
Abstract: Cardioaortic embolism to the brain accounts for approximately 15–30% of ischaemic strokes and is often referred to as 'cardioembolic stroke'. One-quarter of patients have more than one cardiac source of embolism and 15% have significant cerebrovascular atherosclerosis. After a careful work-up, up to 30% of ischaemic strokes remain 'cryptogenic', recently redefined as 'embolic strokes of undetermined source'. The diagnosis of cardioembolic stroke remains difficult because a potential cardiac source of embolism does not establish the stroke mechanism. The role of cardiac imaging—transthoracic echocardiography (TTE), transoesophageal echocardiography (TOE), cardiac computed tomography (CT), and magnetic resonance imaging (MRI)—in the diagnosis of potential cardiac sources of embolism, and for therapeutic guidance, is reviewed in these recommendations. Contrast TTE/TOE is highly accurate for detecting left atrial appendage thrombosis in patients with atrial fibrillation, valvular and prosthesis vegetations and thrombosis, aortic arch atheroma, patent foramen ovale, atrial septal defect, and intracardiac tumours. Both CT and MRI are highly accurate for detecting cavity thrombosis, intracardiac tumours, and valvular prosthesis thrombosis. Thus, CT and cardiac magnetic resonance should be considered in addition to TTE and TOE in the detection of a cardiac source of embolism. We propose a diagnostic algorithm where vascular imaging and contrast TTE/TOE are considered the first-line tool in the search for a cardiac source of embolism. CT and MRI are considered as alternative and complementary tools, and their indications are described on a case-by-case approach.